2015
DOI: 10.1016/j.asoc.2015.03.056
|View full text |Cite
|
Sign up to set email alerts
|

A new fuzzy peer assessment methodology for cooperative learning of students

Abstract: a b s t r a c tIn this paper, a new fuzzy peer assessment methodology that considers vagueness and imprecision of words used throughout the evaluation process in a cooperative learning environment is proposed. Instead of numerals, words are used in the evaluation process, in order to provide greater flexibility. The proposed methodology is a synthesis of perceptual computing (Per-C) and a fuzzy ranking algorithm. Per-C is adopted because it allows uncertainties of words to be considered in the evaluation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…The second part F 2 contained three concepts and six questions. The third part F 3 [6,6,8,10], the crisp output value for learning achievement was 10.33. Table 3 shows the respective ranges of crisp output values for evaluating learning achievement.…”
Section: Building a Range Of Crisp Output Values For Evaluating Learning Achievementmentioning
confidence: 99%
“…The second part F 2 contained three concepts and six questions. The third part F 3 [6,6,8,10], the crisp output value for learning achievement was 10.33. Table 3 shows the respective ranges of crisp output values for evaluating learning achievement.…”
Section: Building a Range Of Crisp Output Values For Evaluating Learning Achievementmentioning
confidence: 99%
“…Very recently, researchers have shown some discrete applications of this artificial intelligence via fuzzy in assessment and evaluation. For instance, Chai et al (2015) have shown an innovative fuzzy peer methodology enhancing cooperative learning of the educands considering the vagueness and imprecision of the words used in the whole course of the evaluation process. Sanchez-Torrubia et al (2012) have attempted to develop a granular linguistic model of a phenomenon (GLMP) to design the learning process as is in the e-learning system and apply the automated generation of the assessment of an assessment report.…”
Section: Artificial Intelligence and Assessment Evaluationmentioning
confidence: 99%
“…A new fuzzy peer assessment methodology which is the synthesis of Per-C and a fuzzy ranking algorithm and considers vagueness and imprecision of words used throughout the evaluation process in a cooperative learning environment, is proposed in (Chai et al, 2015). (Mendel, 2007)…”
Section: Fuzzy Self and Peer Assessmentmentioning
confidence: 99%
“…In general, peer assessment has two types: (i) asking students to assess other students' work in a class; (ii) asking students to assess other students' performance in an identical group (Falchikov, 1995) (Chai, Tay, & Lim, 2015). The rapid development of Internet technologies has led to a dramatic change in educational methods in the last decade.…”
Section: Introductionmentioning
confidence: 99%